2017
DOI: 10.1093/nar/gkx388
|View full text |Cite
|
Sign up to set email alerts
|

A novel double kink-turn module in euryarchaeal RNase P RNAs

Abstract: RNase P is primarily responsible for the 5΄ maturation of transfer RNAs (tRNAs) in all domains of life. Archaeal RNase P is a ribonucleoprotein made up of one catalytic RNA and five protein cofactors including L7Ae, which is known to bind the kink-turn (K-turn), an RNA structural element that causes axial bending. However, the number and location of K-turns in archaeal RNase P RNAs (RPRs) are unclear. As part of an integrated approach, we used native mass spectrometry to assess the number of L7Ae copies that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
2
22
1
Order By: Relevance
“…Phylogenetic and secondary structural analyses revealed that an extension with a K-turn beyond stem P12 is a conserved feature in most archaeal RNase P RNAs (Supplementary Fig. 7) 30,37,38,43,44 .
Fig. 3Structure of the M. jannaschii RPR.
…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic and secondary structural analyses revealed that an extension with a K-turn beyond stem P12 is a conserved feature in most archaeal RNase P RNAs (Supplementary Fig. 7) 30,37,38,43,44 .
Fig. 3Structure of the M. jannaschii RPR.
…”
Section: Resultsmentioning
confidence: 99%
“…The Rpp21/Rpp29 pair was shown to contribute to the pre-tRNA substrate affinity ( 15 ). Additionally, ribosomal protein L7Ae is a part of archaeal RNase P and was shown to bind to kink-turn motifs in RNase P RNA and contribute to the activity and temperature stability of the archaeal RNP ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diversity of the ribonucleoprotein variants of RNase P, and inventory of the multifunctional protein subunits of archaeal/eukaryal RNase P. Overlaid on the secondary structure of the respective RNA subunit are the different RNase P protein subunits. The approximate placement of the protein subunits is based on data reported elsewhere (Tsai et al 2006;Pulukkunat and Gopalan 2008;Xu et al 2009;Chen et al 2010;Reiter et al 2010;Hipp et al 2012;Khanova et al 2012;Fagerlund et al 2015;Lai et al 2017). For subunits that have been demonstrated to have roles other than RNase P catalysis, these are indicated using one-or two-letter codes (see key for explanation of the codes).…”
mentioning
confidence: 99%